Burn injury as a public health problem in Odisha: clinico-epidemiological study of patients admitted in a tertiary care hospital and prospects for control - Sahu, Ranjit Kumar; Chakraborty, Debarati; Jana, Soumen (International Journal Of Community Medicine And Public Health, 2023)
Background: Burn injuries continue to pose a significant and preventable global health challenge, with developing countries like India experiencing a troubling rise in cases. This study aimed to investigate the socio-demographic characteristics and patterns of burn injuries among patients admitted to a tertiary care hospital's. Methods: Over a six-month period, a hospital-based cross-sectional study was conducted using semi-structured questionnaires, with prior consent from patients or their caregivers. Clinical assessments were also conducted to determine the percentage of total body surface area (TBSA) affected and the most severely affected body part. Results: 145 patients included in the study, the females were (56.55%), primarily aged between 21 and 40 years. Hindus (58.62%), lived in rural areas (63.45%), and were married (66.90%). Accidental burns accounted for 81.38% of cases, mainly occurring at home (84.83%). Flame burns were more common among females, while electric burns were more prevalent among males. The majority of burn injuries covered up to 30% of TBSA (44.83%), with the upper limbs being the most severely affected (42.76%). Alarmingly, only 36.55% of patients were admitted on the same day as the injury. Infection (55.86%) and amputation (8.97%) were the most common complications observed, and 14 deaths (9.66%) occurred during the study period. Conclusions: This study highlights the vulnerability of females to flame burns, often stemming from unsafe cooking practices. Delayed hospital admissions were associated with a higher mortality rate. Efforts to promote safety and awareness, particularly in rural areas, are crucial to reducing the burden of burn injuries in India.